1993
DOI: 10.1590/s0034-89101993000100002
|View full text |Cite
|
Sign up to set email alerts
|

Surto de malária induzida entre usuários de drogas injetáveis

Abstract: Em julho de 1990, foi registrado na cidade de Bauru, Estado de São Paulo, Brasil, um surto de malária envolvendo usuários de cocaína injetável. Uma ampla investigação epidemiológica, conduzida de 19 de julho a 13 de setembro, revelou que pelo menos 119 pessoas estavam envolvidas no surto, uma vez que haviam compartilhado seringas e agulhas com um ou mais casos confirmados nos 3 meses anteriores à ocorrência. Cento e duas dessas pessoas foram localizadas e entrevistadas, e destas, 99 foram submetidas a exame de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
7

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 13 publications
0
8
0
7
Order By: Relevance
“…However, the protozoan can be accidentally transmitted by blood transfusion [14] and intravenous drug users [10]. The first case of transfusional malaria was registered in 1911 [15-17]. Although uncommon, transfusional malaria can have serious clinical implications when undetected and not treated early [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, the protozoan can be accidentally transmitted by blood transfusion [14] and intravenous drug users [10]. The first case of transfusional malaria was registered in 1911 [15-17]. Although uncommon, transfusional malaria can have serious clinical implications when undetected and not treated early [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Drug users, who share injecting equipment, are prone to catching certain blood-borne infections, such as HIV and hepatitis B and C. In Brazil, studies suggest that the prevalence of HIV among intravenous drug users is between 40 and 60% (WHO Collaborative Study Group 51 , 1993), that of hepatitis B 40% to 75% (Barata et al 4 , 1993; Carvalho et al 11 1996) and hepatitis C 75% (Carvalho et al 11 , 1996). Studies from other countries suggest the prevalence of hepatitis C among intravenous drug users may surpass that of either hepatitis B or HIV (Crofts et al 15 , 1994 and Majid et al 37 , 1995).…”
Section: Contact Tracingmentioning
confidence: 99%
“…For example, four new cases of HIV were found among six contacts of the first intravenous drug user diagnosed as having HIV in Australia (Blacker et al 7 , 1986). In Brazil, contact tracing has been used to study the transmission of malaria among intravenous drug users (Barata et al 4 , 1993). This study followed an outbreak of five cases of malaria in a non-endemic area (Bauru) where investigation revealed that intravenous cocaine use was the only potential risk factor.…”
Section: Contact Tracingmentioning
confidence: 99%
“…La epidemiología de la enfermedad durante ese período se caracterizó por la persistencia de la transmisión en las áreas maláricas del litoral, reintroducciones esporádicas de casos en el altiplano y un número creciente de casos importados. Después de 1987 los casos en usuarios de drogas inyectadas empezaron a aumentar (20,21).…”
Section: Modelo Focal Y Preventivo 1970 a 1990unclassified